2012
DOI: 10.1080/17457823.2012.661591
|View full text |Cite
|
Sign up to set email alerts
|

Disassembling the classroom – an ethnographic approach to the materiality of education

Abstract: To cite this article: Tobias Roehl (2012) Disassembling the classroom -an ethnographic approach to the materiality of education, Ethnography and Education, 7:1, 109-126,The ethnography of education is challenged by the materiality of the classroom. Ethnographic accounts of school lessons mostly highlight language and interaction and offer no suitable methodology for researching objects and their role in the classroom. Moreover, objects are part of complex and interwoven assemblages involving human actors, prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…With these limitations in mind, we suggest that engaging solely in interview research entails the risk of becoming an anthropocentric research approach that fails to capture our everyday intertwinement with material artifacts. Only by including material presence in their analyses can qualitative psychologists overcome such "humanist bias" (Roehl, 2012a). Our own strategy of circumventing humanist bias is a methodological analogue to the oscillation between meaning and presence, namely oscillating between interviews and participant observation.…”
Section: Qualitative Methodologies: Including Participant Observationmentioning
confidence: 99%
“…With these limitations in mind, we suggest that engaging solely in interview research entails the risk of becoming an anthropocentric research approach that fails to capture our everyday intertwinement with material artifacts. Only by including material presence in their analyses can qualitative psychologists overcome such "humanist bias" (Roehl, 2012a). Our own strategy of circumventing humanist bias is a methodological analogue to the oscillation between meaning and presence, namely oscillating between interviews and participant observation.…”
Section: Qualitative Methodologies: Including Participant Observationmentioning
confidence: 99%
“…Our study has indicated the potential of using mobile phones as e-networked tools to support inquiry-learning processes. The study revealed aspects of mediality and perfomativity (Roehl, 2012) through how students engaged with mobile phones as material objects as well as how the networking technology affected them in shaping their engagement in class during their science inquiry. While the use of mobile phones in schools has been reported to present new pedagogical opportunities (Looi et al, 2015) we found that this was shaped by the sociocultural conditions of technology use.…”
Section: Resultsmentioning
confidence: 99%
“…A realist rendering of the data in which it is assumed that learning space is given in advance of practice and functions as a clear agent for change (Joint Information Systems Committee 2006) can provide much needed information about the impacts of newly designed learning spaces on learning and related pedagogic processes, however, significant occlusions occur in such a rendering. While human meaning-makinginteraction and discourse − is attended to, the materiality of pedagogy (Ellsworth 2005) and the material dimensions of education (Kalthoff and Roehl 2011;Roehl 2012) slip from view. The data demonstrate that material objects such as newly designed physical spaces are neither just there waiting to be occupied or used, with the teacher, getting almost tutored, and that's more available to me when there's a portable whiteboard maybe around the corner or something, and I can just call a teacher and say, 'hey, I need help with this, can you come help me?'…”
Section: Methodsmentioning
confidence: 99%